(untitled) (Estudos em Design, 2015)
This paper discusses the competences worked by teachers in the disciplines of Design Product Design. Identified through a qualitative study in which in-depth interviews were developed with teachers of Product Design, competences of graphic representation, modeling, verbal expression, teamwork, empathy, autonomy are exposed and discussed. The results show its characteristics and how these are developed throughout the disciplines of Product Design.